Internalisasi Nilai-Nilai Pendidikan Agama Islam dalam Membentuk Karakter Religius melalui Metode Pembiasaan Shalat Berjamaah di SDN Andonosari I Tutur Pasuruan - Samsul Arifin; Mohammad Asrori (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze how the internalization of Islamic Religious Education (PAI) values ​​can shape students' religious character through the method of habituating congregational prayer at SDN Andonosari I Tutur Pasuruan. The formation of students' religious character is very important in education, especially in facing the challenges of globalization and the shift in social values ​​that occur in society. For this reason, an effective approach is needed to instill Islamic religious values ​​in students' daily lives. The method used in this study is a descriptive qualitative method with a case study approach. Data collection was carried out through direct observation, interviews with PAI teachers, principals, and parents of students, as well as documentation related to habituation activities at school. This study also analyzes the application of Islamic religious values ​​in students' daily routines, such as congregational prayer activities, dhikr, and other activities related to noble morals and discipline. The results of the study indicate that the application of the habituation method in internalizing Islamic religious values ​​at SDN Andonosari I Tutur Pasuruan has a significant impact on the formation of students' religious character. Habituation through daily activities, such as congregational dhuha prayer, congregational dhuhur prayer and other good habits, can form a religious attitude that is reflected in students' behavior in the school environment and society. In addition, the active involvement of parents and teachers in supporting this habituation also strengthens the results of the internalization of Islamic religious values ​​in students. This study concludes that the habituation method has a very important role in instilling Islamic religious values ​​as a whole. Therefore, collaboration between schools, families, and communities is needed in supporting the process of internalizing Islamic religious values ​​to form a strong religious character in students. This study is expected to be a reference for the development of Islamic-based character education strategies in elementary schools in Indonesia.